2005
DOI: 10.1590/s1516-635x2005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Pearl millet utilization in ccommercial laying hen diets formulated on a total or digestible amino acid basis

Abstract: An experiment was carried out to evaluate the effect of replacing corn with pearl millet in commercial layer diets, formulated according to the minimal requirements for total and digestible amino acids. Two hundred and forty Lohmann LSL laying hens with 25 weeks of age were distributed in a completely randomized experimental design according to a 2 x 5 factorial arrangement with 3 replicates of 8 birds. Feed was formulated on two amino acid basis (total or digestible) according to Rostagno et al. (2000) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
3
4
1
1
Order By: Relevance
“…interaction between substitution and age treatments had the same effect in higher egg production for control and 30% substitution treatment for early ages of laying eggs 25-28 weeks of age and then the production decrease for the rest of the ages for all treatments. We found the same effect on HD%, the means for the four treatments (26.07, 18.40, 23.10, and 18.70), respectively with the same significant difference, These results were inconsistent with [15], in laying hens, while this finding was consistent with findings [8,10,15]. The decrease in the number of eggs by increasing the substitution of millet in the diet and this is likely due to the high percentage of fiber in the millet diet, which leads to an increase in the speed of food passage in the gut and less benefit from it [16].…”
Section: Effect Of Substitution Millet Energy Instead Of Yellow Corn Energy and Age On Production Period 25-33 Weekssupporting
confidence: 72%
See 2 more Smart Citations
“…interaction between substitution and age treatments had the same effect in higher egg production for control and 30% substitution treatment for early ages of laying eggs 25-28 weeks of age and then the production decrease for the rest of the ages for all treatments. We found the same effect on HD%, the means for the four treatments (26.07, 18.40, 23.10, and 18.70), respectively with the same significant difference, These results were inconsistent with [15], in laying hens, while this finding was consistent with findings [8,10,15]. The decrease in the number of eggs by increasing the substitution of millet in the diet and this is likely due to the high percentage of fiber in the millet diet, which leads to an increase in the speed of food passage in the gut and less benefit from it [16].…”
Section: Effect Of Substitution Millet Energy Instead Of Yellow Corn Energy and Age On Production Period 25-33 Weekssupporting
confidence: 72%
“…There was no significant difference between control and millet substitution treatments for weight gain (33.75, 35.65, 35.94 and 34.69) g respectively, these results were agreed with [13], in broiler at 14 and 21 days old and [15], in laying hens. There was a significant increase (P <0.05) of FC /bird/week for substitution treatment 30% on control treatment and a numerical increase on the other two millet substitution treatments, control, and substitution treatments means (66.80, 74.63, 80.27 and 74.41) g / bird/week respectively, These results were not agreed with [13], in broiler at ages 14 and 21 days and [10,15], in laying hens. There was no significant effect of millet substitution treatments 20%, 30%, and 40% in FCR, these results were agreed with [13], in broiler chicks at ages 14 and 21 days.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…A energia do milheto é relativamente alta, em razão do seu maior conteúdo de óleo em comparação ao do milho, do trigo e do sorgo (Luis et al, 1982;Hill & Hanna, 1990;Haydon & Hobbs, 1991;Adeola et al, 1994). De acordo com Filardi et al (2005), o milheto contém aproximadamente 85% do conteúdo energético do milho. Mogyca et al (1994) testaram diversos níveis de milheto em substituição ao milho em rações para frangos de corte e concluíram que esse grão constitui boa fonte de energia para frangos de corte.…”
Section: Introductionunclassified
“…According to Izge et al (2007), it is a nutritious crop, producing almost all the required nutrients needed by humans. Filardi et al (2005) reported that pearl millet produces higher protein levels than maize and have approximately 85% of energy content of maize.…”
Section: Introductionmentioning
confidence: 99%